Review Analysis of the Association between the Prevalence of Activated Brown Adipose Tissue and Outdoor Temperature. (19th April 2012) - Huang, Yung-Cheng; Hsu, Chien-Chin; Wang, Pei-Wen; Chang, Yen-Hsiang; Chen, Tai-Been; Lee, Bi-Fang; Chiu, Nan-Tsing
Abstract : Brown adipose tissue (BAT) is important for regulating body weight. Environmental temperature influences BAT activation. Activated BAT is identifiable using F 18 -fluorodeoxyglucose positron emission tomography/computed tomography (F 18 -FDG PET/CT). F 18 -FDG PET/CT scans done between June 2005 and May 2009 in our institution in tropical southern Taiwan and BAT studies from PubMed (2002–2011) were reviewed, and the average outdoor temperatures during the study periods were obtained. A simple linear regression was used to analyze the association between the prevalence of activated BAT (P ) and the average outdoor temperature (T ). The review analysis for 9 BAT studies (n = 16, 765 ) showed a significant negative correlation (r = - 0.741, P = 0.022 ) between the prevalence of activated BAT and the average outdoor temperature. The equation of the regression line is P ( % ) = 6.99 − 0.20 × T   ( C ∘ ) . The prevalence of activated BAT decreased by 1% for each 5 C ∘ increase in average outdoor temperature. In a neutral ambient temperature, the prevalence of activated BAT is low and especially rare in the tropics. There is a significant linear negative correlation between the prevalence of activated BAT and the average outdoor temperature.